Chemo-radiotherapy for olfactory neuroblastoma: cases report and literature review - Wu, Jeng-You; Chiou, Jeng-Fong; Ting, Lai-Lei (Therapeutic Radiology and Oncology, 2019)
A 48-year-old female patient diagnosed as olfactory neuroblastoma was treated by radiotherapy 70 Gy in 35 fractions (2 Gy per fraction) to right nasal mass, right ethmoid sinus mass, bilateral upper 2/3 neck lymphadenopathy in 2010, and concurrent intravenous Cisplatin 30 mg/m2 for one course. Tumor was gradually decreased in size without recurrence for 9 years. The second case was a 38-year-old male patient treated with induction chemotherapy by intravenous Etoposide + carboplatin for 4 courses during March to May in 2011 and followed by radiotherapy 70 Gy in 35 fractions (2 Gy per fraction) to ethmoid mass & bilateral level IIa lymphadenopathy during June to August in 2011. He was disease free without recurrence for 8 years. These two cases demonstrated that definitive chemo-radiotherapy would be an alternative treatment option for locally advanced olfactory neuroblastoma. They received definitive chemo-radiotherapy and experienced good local control without recurrence for more than 8 years. However, the further study for optimal regimen of chemotherapy is warranted.